Ermolenko S. V. Тo the question about uniform structure of the language - Ermolenko S. V. (Philological Treatises, 2020)
This article deals with the legitimacy of existence of dialects, regiolects and other forms of one uniform language of the certain people, one nation. Existence of different versions of one language is attempt to keep the identity with people, ancestors and traditions. Each language is not homogeneous and constant changes take place in it. It is the barometer of all the processes that occur in every nation.